Cruise 64PE400: Hydrographic survey of the Irminger Sea in July 2015 for the Overturning in the Subpolar North Atlantic Program (OSNAP) ... - De Jong, Marieke; De Steur, Laura (SEANOE, 2019)
During cruise 64PE400 the OSNAP East moorings, which were deployed in the Irminger Basin in summer 2014 have been recovered, serviced and redeployed. There are 5 moorings in the eastern Irminger Sea in the Irminger Current (IC) maintained by NIOZ, 5 moorings in the Western Irminger Sea in the Deep Western Boundary Current (DWBC) maintained by NOC, and one mooring (LOCO2) in the centre of the Irminger gyre (section 4) maintained by NIOZ. A total of 34 RAFOS floats were released at target depths between 1800 and 2200 m in the eastern and western Irminger Sea as part of the US OSNAP program (see cruise report). The mooring work was complemented with repeat CTD stations on the former WOCE (or current CLIVAR) AR7E repeat section (between roughly 59°N, 31°W and 60°N, 42.5°W) including sampling for salinity and dissolved oxygen (O2) calibration. On the westernmost CTD stations in the East Greenland Current samples for ∂18O and nutrients were also taken.A second short CTD section was carried out on the Greenland ...